Experimental and numerical study of the effect of elevated pressure on laminar burning velocity of lean H2/CO/O2/diluents flames. (1st August 2020) - Wang, Shixing; Wang, Zhihua; Han, Xinlu; Chen, Chenlin; He, Yong; Zhu, Yanqun; Cen, Kefa
Highlights: The burning velocities of H2 /CO/O2 /diluent at high pressure (11 bar) were measured. Five syngas mechanisms were tested and show mixed agreement depending on pressure. Low flame temperatures cause negative pressure dependence of mass burning rate. Sensitivities and HO2 mole fraction show non-monotonic pressure dependence. The change of the flame front height can be used to validate reaction mechanisms. Abstract: Laminar burning velocities ( S L ) of H2 /CO/O2 /diluents (He or N2 ) were reported at lean conditions ( ϕ  = 0.5–1.0), elevated pressures (1–11 bar) and a wide range of H2 -CO volumetric ratios. A new high-pressure rig based on specially designed heat flux burner was applied to obtain planar, adiabatic and stretch-less flames used for laminar burning velocity measurements. Five popular syngas oxidation mechanisms were tested against the obtained S L data and showed satisfactory agreement even at high pressures up to 11 bar. S L decreases as pressure increases while the negative pressure dependence of mass burning rate is experimentally and numerically found for syngas with high diluent content in the oxidizer or high hydrogen content in the fuel, which indicated the negative dependence of the overall reaction order on adiabatic flame temperature. Sensitivity and rate of production analyses indicated that the sensitivity coefficients and HO2 mole fraction increase to the maximum at the pressure of the minimum overall reaction order and then decreases, which leads to larger uncertainty on predicting S L at higher pressures. The flame front height represented by the peak OH* chemiluminescence location also shows a non-monotonic variation trend as pressure increases and can serve as a target for mechanism validation.